Writing Errors of Engineering Students: Reflections on Teaching and Assessment - Riaz, Mehvish (University of Wah Journal of Social Sciences, 2021)
The study emphasizes the importance of accuracy in students’ writings and the responsibilities of teachers in this regard. It aims at inspiring the teachers and learners of science and engineering to concentrate more on learning English and hone their writing skills. An error analysis of the paragraphs written by the engineering students at UET, Lahore has been done. Frequencies of the errors of tenses, capitalization, word choice, spellings, articles, and prepositions have been checked. A sample of 25 students has been selected randomly from different departments and data have been analyzed qualitatively. Results suggest that engineering students make errors of tenses and word choice the most. Issues regarding capitalization, spelling, punctuation, translation, organization, coherence, and editing have also been found. Students make errors of omission, transfer, addition, mis-ordering, and misinformation as suggested by Ellis (1994). Suggestions have been made for teachers to adopt task-based methods for teaching writing skills, use varied materials, check the assignments, give feedback and make the writing process interesting for learners so that the 21st century challenges can fairly be met.